A network analysis approach to the relationship between fear of missing out (FoMO), smartphone addiction, and social networking site use among a sample of Chinese university students. (March 2022) - Li, Li; Niu, Zhimin; Mei, Songli; Griffiths, Mark D.
Abstract: Background and aims: Previous research has explored the relationship between fear of missing out (FoMO), social network site (SNS) use, and/or smartphone addiction by correlation analysis and construction of latent variables model. However, smartphone addiction may also intensify negative emotion (e.g., fear of missing out, anxiety, and depression) and risky behavior (e.g., excessive social media use and problematic smartphone game activities). To date, few studies have adopted a network analysis approach to investigate the reciprocal action between the aforementioned variables. Therefore, the present study used network analysis to evaluate the relationship between FoMO, SNS use, and smartphone addiction among a sample of Chinese university students. Methods: A sample comprising 1258 Chinese university students (502 males) completed a survey including the Chinese Trait-State Fear of Missing Out Scale (T-SFoMOSC), Mobile Phone Addiction Index (MPAI), and Social Network Site Intensity Scale (SNSIS). Results: Inability to control craving and productivity loss had the closest edge intensity. Feeling anxious and lost was the strongest central node (betweenness = 1.903, closeness = 1.853, strength = 1.287) in the domain-level network. The item-level network analysis showed that FoMO was positively associated with SNS use and smartphone addiction. There were no significant gender differences in the network structure and the global edge strength. Conclusions: The findings here indicate that there is a close relationship between FoMO, SNS use, and smartphone addiction. Excessive social media use and higher level of FoMO appear to play a contributory role in smartphone addiction. Smartphone addiction may also further increase excessive SNS use and increase the level of FoMO. A bidirectional influence between smartphone addiction, SNS use and FOMO should be considered. Gender differences in FoMO, smartphone addiction, and motivation of SNS use should be investigated in future research. Highlights: Network analysis has rarely been used to examine smartphone addiction. Inability to control craving and productivity loss had the closest edge intensity. Feeling anxious and lost was the strongest central node in the domain-level network. The relationship between FoMO, SNS use, and smartphone addiction was close in the item-level network. There were no significant gender differences in the network structure and the global edge strength.